2021
DOI: 10.1021/acs.joc.1c00768
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Mediated Amine Oxidation and Beyond: A Solvent-Free, Flow-Chemistry Approach

Abstract: Ozone is a powerful oxidant, most commonly used for oxidation of alkenes to carbonyls. The synthetic utility of other ozone-mediated reactions is hindered by its high reactivity and propensity to over-oxidize organic molecules, including most solvents. This challenge can largely be mitigated by adsorbing both substrate and ozone onto silica gel, providing a solvent-free oxidation method. In this manuscript, a flow-based packed bed reactor approach is described that provides exceptional control of reaction temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Because calculations of ozone suffer from orbital instability (singlet–triplet instability); therefore O 3 , intermediates, and transition states are treated as diradical with unrestricted UM06-2X calculations . It is noticed that the ozonolysis of amines in the gas phase is different from that in the aqueous phase where formation of N -oxide dominates by transferring an O atom from ozone to nicotine forming amine- N ′-oxide. …”
Section: Resultsmentioning
confidence: 99%
“…Because calculations of ozone suffer from orbital instability (singlet–triplet instability); therefore O 3 , intermediates, and transition states are treated as diradical with unrestricted UM06-2X calculations . It is noticed that the ozonolysis of amines in the gas phase is different from that in the aqueous phase where formation of N -oxide dominates by transferring an O atom from ozone to nicotine forming amine- N ′-oxide. …”
Section: Resultsmentioning
confidence: 99%
“…The AP-SiO 2 (Scheme ) used here is part of a widely studied class of functionalized materials with applications in CO 2 capture and heterogeneous catalysis. , This class of materials was chosen for several reasons, including (1) the distinct IR features of the organic functionality and oxidation products (e.g., NO X ), (2) their straightforward synthesis onto silica supports, (3) the high achievable loading of the 3-aminopropyl groups onto the SBA-15, and (4) the existing literature characterizing the behavior and stability of primary amines in oxygen environments. For example, several previous works have reported that primary amines will oxidize at low temperatures in the presence of reactive oxygen derivatives such as ozone (O 3 ). This process was shown to selectively form nitroalkanes in high yields without oxidizing the carbon framework. Therefore, we hypothesized the oxygen plasma would similarly generate nitroalkane derivatives from the primary amines on AP-SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of NTP to perform this transformation obviates the need for harmful reactants that would typically be used (e.g., hypofluorous acid, Caro's acid, and organic peroxides), and the resulting nitro groups can be readily converted to other desired functional groups. 73 This has clear applications in the synthesis of biomaterials, where surface hydrophobicity needs to be carefully controlled to either prevent or promote the adhesion of cells and the growth of biofilms. 87 The plasma transmission cell was capable of monitoring the evolution of surface-bound species over time, demonstrating its usefulness as an in situ characterization technique.…”
Section: Application 1: Plasma Oxidation Of Primary Amine-functionali...mentioning
confidence: 99%
“…Subsequently, Newman et al reported a flow-based packed bed reactor lead to tame the ozone-mediated oxidation of amines into the corresponding nitro derivatives. 32 The reaction temperature and time need to be strictly controlled due to the powerful oxidant (O 3 , ozone). Herein, we hypothesized that continuous-flow synthesis of nitro heteroarenes from amines can act as a facile and sustainable alternative instead of traditional oxidation batch processes.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine gas, water, and acetonitrile were pumped by sequential gas–liquid/liquid–liquid continuous-flow procedures. Subsequently, Newman et al reported a flow-based packed bed reactor lead to tame the ozone-mediated oxidation of amines into the corresponding nitro derivatives . The reaction temperature and time need to be strictly controlled due to the powerful oxidant (O 3 , ozone).…”
Section: Introductionmentioning
confidence: 99%